Immune checkpoint inhibitor-induced diabetes can potentially be effectively treated with infliximab: a case report of two patients - Savion Gaiger, Noam; Hurwitz, Michael E.; Hafez, Navid; Kluger, Harriet M.; Herold, Kevan C.; Perdigoto, Ana Luisa (Frontiers in Endocrinology, 2025)
Immune checkpoint inhibitor-induced diabetes is a potentially severe and life-threatening complication of immune checkpoint inhibitor therapy in patients with advanced malignancies. It is typically an irreversible complication due to the complete destruction of pancreatic beta cells that requires ongoing insulin treatment, and patients often exhibit labile diabetes. Inflammatory cytokines, including TNF-α, are thought to play a role in the development of this form of diabetes, as they do in spontaneous autoimmune diabetes. TNF-α has also been implicated in the development of other immune-related adverse events caused by immunotherapy, and infliximab, a TNF-α monoclonal antibody, has shown efficacy in several of these complications. We tested whether infliximab could preserve beta-cell function in immune checkpoint inhibitor-induced diabetes. We present two cases in which infliximab treatment appeared to halt beta-cell destruction, as evidenced by maintenance of C-peptide levels, as well as improved clinical outcomes in terms of diabetes control.